2016
DOI: 10.1007/s40333-016-0059-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of converting natural grasslands into planted grasslands on ecosystem respiration: a case study in Inner Mongolia, China

Abstract: With increasingly intensifying degradation of natural grasslands and rapidly increasing demand of high quality forages, natural grasslands in China have been converted into planted grasslands at an unprecedented rate and the magnitude of the conversion in Inner Mongolia is among the national highest where the areal extent of planted grasslands ranks the second in China. Such land-use changes (i.e., converting natural grasslands into planted grasslands) can significantly affect carbon stocks and carbon emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…For A*B, GWP were affected by SOM, NO 3 − , TN, and salinity. This is consistent with previous reports that showed that Bro has a higher salt and alkali tolerance; therefore, it is mainly regulated by soil nutrients, whereas Alf has less nutrient limitation due to nitrogen fixation, and A*B is regulated by nutrient competition and salinity (Figure 5) (Lucero et al, 2000;Zhang et al, 2017;Jia et al, 2018). Regarding NG and artificial grasslands, SOM had different effects on GWP (Figure 5).…”
Section: Drivers Of Gwp Effects In Different Types Of Grasslandsupporting
confidence: 91%
See 1 more Smart Citation
“…For A*B, GWP were affected by SOM, NO 3 − , TN, and salinity. This is consistent with previous reports that showed that Bro has a higher salt and alkali tolerance; therefore, it is mainly regulated by soil nutrients, whereas Alf has less nutrient limitation due to nitrogen fixation, and A*B is regulated by nutrient competition and salinity (Figure 5) (Lucero et al, 2000;Zhang et al, 2017;Jia et al, 2018). Regarding NG and artificial grasslands, SOM had different effects on GWP (Figure 5).…”
Section: Drivers Of Gwp Effects In Different Types Of Grasslandsupporting
confidence: 91%
“…In contrast, non-legume wheatgrass exhibits better drought and salinity tolerance than purple prairie clover (Gong et al, 2015;Jia et al, 2018), which may explain why Alf had lower FCO 2 and higher SOM levels (Li et al, 2012). The higher emissions and lower carbon storage in mixed-species grasslands could be attributed to the complementary competition among different species (Figures 2D, 4E) (Lucero et al, 2000;Zhang et al, 2017). The mixture of legumes and grasses promotes better nutrient supply, and competition among plants stimulates rhizosphere effects by producing more types of root exudates, consequently jointly promoting respiration intensity in the soil layer.…”
Section: Fco 2 Response To Different Grassland Typesmentioning
confidence: 99%
“…However, soil carbon pool dynamics can be altered with the factors like climate change [40], land use [41] [42] [43] and management practices [21] [44] [45] [ 46]. Research indicated that global soil carbon dioxide emissions are in the range of 98 ± 12 Pg•y −1 (1 Pg = 10 15 g), with annual increases of 0.1 Pg that is suggested to be temperature-associated [47].…”
Section: Introductionmentioning
confidence: 99%
“…Geographical distribution of grassland is expansive throughout the world [38] and it is one of the principal ecotypes in the terrestrial ecosystem situated mostly in areas with more severe eco-environment where neither the forest growth nor the farmland reclamation is appropriate. Carbon in grasslands originates from below-ground biomass [14] [21] [52], primarily roots [53] [54] that increase with the age [55] and micro-organisms [43]. Approximately above 40% land area of the global terrestrial ice-free surface is covered by grasslands [56].…”
Section: Introductionmentioning
confidence: 99%
“…Existing measures of happiness mainly adopt univariate scoring measures of individual or family life satisfaction, but since happiness is difficult to directly observe, scoring measures are also susceptible to the influence of actual interview bias and respondents' emotional changes, resulting in distorted results of happiness and leading to measurement bias. Therefore, in light of the happiness measurement methods and research definitions of Xing [7], Tan et al [48], and Zhang et al [49], and based on the availability of research data and the sustainability of forest resource utilization, this study deconstructs the happiness of forest farmers' families into five dimensions: family environment, economic status, educational conditions, public services, and developmental resilience. Among them, family environment measures the basic living conditions and water security of forest farmers' families; economic condition evaluates the subjective feeling of forest farmers regarding family income and local socio-economic development; educational condition measures the perception of social education and the degree of education of forest farmers' families; public services targets the subjective perception of forest farmers regarding local social recreation, employment, and basic public service security; and developmental resilience embodies the forest farmers' families in terms of natural disasters, epidemic shocks, and the prevention of returning to poverty (Table 1).…”
Section: Variable Selection and Descriptive Statisticsmentioning
confidence: 99%